Effects of Huolisu Oral Solution on Depression-Like Behavior in Rats: Neurotransmitter and HPA Axis - Xiao, Min; Xie, Kaiyong; Yuan, Li; Wang, Jun; Liu, Xing; Chen, Zhonghua (Frontiers in Pharmacology, 2022)
Background: Depression is a common mental disorder, and its morbidity rate is expected to rank second among all mental disorders by 2020. Hence, traditional Chinese medicines gradually attract the attention of many researchers because of various targets and low toxicity. Huolisu oral solution (HLS) is a Chinese medicine compound preparation, which is present in the Chinese Pharmacopoeia. It is used clinically mainly for the treatment of neurasthenia, perimenopausal syndrome, and insomnia or depression associated with cerebrovascular disease. Despite the fact that HLS has been used as an anti-depressant in clinics, the underlying mechanism is still an untouched domain. To provide a theoretical basis for the clinical application, a series of assessment methods, such as tail suspension test (TST), forced swim test (FST), locomotor activity test in mice and rat models of chronic unpredictable mild stress (CUMS), have been done in our study. Objective: Our aim was to explore the anti-depressive effect and mechanism of HLS. Methods: The CUMS was induced in rats to simulate a depressive-like behavior. Neurotransmitters and hormones were detected by enzyme-link immunosorbent assay (ELISA). Pathomorphology examination of the hippocampus was obtained by the TSView7 image analysis system. The active ingredients of HLS were also determined using high-performance liquid chromatography (HPLC). Results: HLS could alleviate depressive-like behavior of the model rats. Biochemical analysis showed that HLS enhanced the levels of 5-hydroxytryptamine (5-HT), norepinephrine (NE) and dopamine (DA) in hippocampus and diminished these in serum of the CUMS rats. HLS could also decreased the concentration of corticosterone (CORT), adrenocorticotropic hormone (ACTH) and β-endorphin (β-EP) in blood. Pathohistological examination revealed that hippocampus and adrenal gland were improved after treatment with HLS. Conclusions: This study concluded that HLS could alleviate depressive-like behaviors in the rats exposed to CUMS, and the potential mechanism may be related to the regulation of the monoamine neurotransmitters, the hypothalamic-pituitary-adrenal (HPA) axis and the β-EP. These findings hint that HLS is likely to be a potentially effective agent for treating depression.